Effects of concentric and eccentric strength training on fatigue induced by concentric and eccentric exercises - Cadore, E. L.; González-Izal, M.; Grazioli, R.; Setuain, I.; Silveira Pinto, R.; Izquierdo, M. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To compare the concentric and eccentric training effects on fatigue induced by eccentric and concentric protocols. Methods: A total of 22 men and women (22 [3.6] y) were assigned to concentric (GCON, n=11) or eccentric training (GECC, n=11). The concentric (CON) and eccentric (ECC) protocols were composed of 4 sets of 20 knee-extension/flexion repetitions. Force losses were analyzed by comparing 10 repetitions` mean torques during the protocols and by verifying the maximal voluntary contraction and rate of torque development before and after the protocols. Muscle damage was assessed using echo intensity of the vastus lateralis 48 h after the protocols. Training consisted of 6 wk of isokinetic exercise at 60°/s (concentric or eccentric) twice weekly. Results: Before training, both protocols resulted in dynamic and isometric force losses in GCON and GECC (P<.01), but the magnitude was greater after the CON protocol than after the ECC protocol (P<.001). After training, both GCON and GECC showed similar force decreases during the CON and ECC protocols (P<.01), and these changes were not different from the pretraining decreases. Regarding maximal voluntary contraction after training, GECC showed lower force decreases than GCON after ECC exercise (-13.7% vs -22.3%, respectively, P<.05), whereas GCON showed lower maximal voluntary contraction decreases after CON exercise compared with pretraining (-29.2%, P<.05). Losses in rate of torque development were similar after the protocols before and after the training regimens. No changes in echo intensity were observed after the protocols before and after training. Conclusion: Both interventions resulted in similar force decreases during fatigue protocols compared with those associated with pretraining.